Proceso de atención de enfermería en paciente de 18 años de edad con vaginitis viral - Monserrate Bravo, Nohely Arianna (2018)
The vagina is the organ of the female genital system that connects the uterus to the outside of the body. It is formed by a pathway covered with mucous membranes that maintain moisture and acidity and protect against possible infections, and its orifice is located between the urethra and the anus. Vaginitis refers to an inflammation or infection of the vagina. It is a common gynecological problem for women of all ages. One third of women have at least one type of vaginitis at some point in their lives. Genital herpes is a type of viral vaginitis caused by the herpes simplex virus (HSV) that is transmitted through intimate contact with the lining of the mucous membranes of the mouth or vagina or the skin of the genitals. Viral vaginitis is an infection of the vagina that may be caused by the genital herpes virus or by the human papillomavirus (HPV).